Percepción cooperativa de las cofradías de pescadores: un estudio empírico - CERVERA PAZ, Ángel (REVESCO. Revista de Estudios Cooperativos, 2010)
Spain’s Legal framework defines Fishing Guilds as Public Law Associations, thus linking and associating them to the authorities, and making them dependent on Spain’s Central and Regional governments. Nonetheless, a detailed analysis of Guilds will let us conclude that, apart from being Public Law Associations, Guilds could be classified within the Social Economy framework due to its many other features. First of all, a revision of the bibliography has been made concerning two thematic modules: Fish Guilds: their historical evolution and issues affecting them and Social Economy companies regarding Fishing Guilds. Next, an empirical analysis has been carried out with the aim of accounting for the Guilds’ specific issues by directly asking the people in charge, so as to go into the Guilds’ qualitative aspects in detail. This will allow us to show why Guilds should belong to the Social Economy by searching for the values and principles shared by Social Economy companies within the Guilds’ area. Ours is an empirical-descriptive work. Descriptive, as it is mainly based on the description of a “group, community or institution whose main elements and features are being analysed. Empirical, as it involves a piece of research whose aim is the study of a given reality by way of either observing or experiencing what is going on in such a reality (SIERRA, 2002). Moreover, this work meets CHAVEs (1999) and SANCHÍS (2001)’s proposal who point out that “the scientific study of Social Economy should be carried out within a multidisciplinary environment, contributing an integrated and global perspective”.
Keywords: Fishermen’s Associations; Public Law Corporations; Democratic Management; Autonomous Organizations; Self-Help